Small volume excitation and enhancement of dye fluorescence on a 2D photonic crystal surface - Estrada, Laura Cecilia (2010)
We demonstrate an easy-to-implement scheme for fluorescence enhancement and observation volume reduction using photonic crystals (PhCs) as substrates for microscopy. By normal incidence coupling to slow 2D-PhC guided modes, a 65 fold enhancement in the excitation is achieved in the near field region (100 nm deep and 1 μm wide) of the resonant mode. Such large enhancement together with the high spatial resolution makes this device an excellent substrate for fluorescence microscopies.